Use of wordwall in learning models discovery learning in science subjects to create pancasila student profile - Mursalin, Muhammad; Sanjaya, Dewa Bagus; Suma, Ketut (Universitas Tanjungpura, 2025)
This study aims to describe the application of Wordwall media in the Discovery Learning model in Natural and Social Sciences (IPAS) subjects and analyze its contribution in shaping the Pancasila Student Profile. The Discovery Learning model was chosen because it can encourage students to actively discover concepts independently, while Wordwall is used as an interactive medium to support this process. The research method used is a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The results show that the integration of Wordwall in each stage of Discovery Learning can improve learning activities and shape student character, especially in the dimensions of critical thinking, mutual cooperation, and independence. This media also strengthens student learning interest and creates a fun and meaningful learning atmosphere. Thus, the strategic use of Wordwall in IPAS learning has the potential to be an effective tool to support the implementation of the Independent Curriculum and strengthen the values of the Pancasila Student Profile